Compressive Strength of Cement Mortar Affected by Sand Microfiller Obtained with Collision Milling in Disintegrator. (2017) - Bumanis, Girts; Bajare, Diana
Abstract: The cement and concrete industries are continuously searching for new effective microfillers which could be obtained with relatively low cost, are wide spread and which improves most important concrete properties – strength and durability. Traditionally fine sand is used as inert mineral filler to the concrete mixture to make material structure compact in micro level. To obtain powder mineral filler material often milling is used to reduce particle size distribution and morphology of obtained particles. Traditionally planetary ball milling is applied, however this method is ineffective if large quantity of material should be prepared. Grinding by collision is more effective method for refining of brittle material and one of the few machines for material grinding by collision is disintegrator. Current research deals with natural quartz, dolomite screening and natural quartz-dolomite mixed sand milling by collision in disintegrator at different energy rates and tested as micro filler in portland cement mortar as partial sand replacement. The time factor of sand storage after disintegration was investigated to detect potential changes of sand particle properties during milling. Results indicate that cement mortar prepared with disintegrated sand right after disintegration provides compressive strength increase up to 20% comparing to reference mixture and the time factor of disintegrated sand is significant to remain increased compressive strength results.